Ca(2+)-independent nitric oxide synthase activity in human lung after cardiopulmonary bypass. Issue 4 (April 1995) - Delgado, R; Rojas, A; Glaría, L A; Torres, M; Duarte, F; Shill, R; Nafeh, M; Santin, E; González, N; Palacios, M
Abstract : BACKGROUND–Because surgery involving cardiopulmonary bypass induces a systemic inflammatory response, the effect of cardiopulmonary bypass on nitric oxide (NO) generation was investigated in human lung tissue. METHODS–Nitric oxide synthase (NOS) activity was measured by the conversion of 14C-L-arginine to 14C-L-citrulline in tissue biopsy samples obtained before and after cardiopulmonary bypass. RESULTS–The Ca(2+)-independent production of NO found before cardiopulmonary bypass was extremely low (1.5 (0.5) pmol citrulline/mg/min), but was increased after the bypass operation (23.6 (11) pmol/mg/min). CONCLUSIONS–Ca(2+)-independent NOS activity was detected in human lung after cardiopulmonary bypass. This finding may provide an important insight into the pathogenesis of the tissue damage and acute phase response observed after such surgery.